How the Clamping Distance of the Umbilical Cord affects Microbial Colonization and Cord Separation Time: A Randomized Trial - Akyildiz, Deniz; Coban, Ayden (Puerto Rico Health Sciences Journal, 2023)
Objective: This study aimed to explore how umbilical cord separation time and microbial colonization are affected by umbilical cord clamping distance. Methods: The randomized controlled study included 99 healthy newborns and was conducted at a hospital in Kahramanmaras, Turkey. The newborns were randomly divided into 3 groups: intervention group I (cord length: 2 cm); intervention group II (cord length: 3 cm; control group (not measured). On postpartum day 7, a sample of the umbilical cord was taken to assess microbial colonization. The mothers were contacted via mobile phone on the 20th day for an at-home follow-up. The data were analyzed by applying Pearson’s chi-square test, Fisher’s exact test, a 1-way analysis of variance test, and Tukey’s post hoc Honest Significant Difference test. Results: The mean umbilical cord separation time of the newborns was found to be 6.9 (±2.1) days in the intervention group I, 8.8 (±2.9) days in the intervention group II, and 9.5 (±3.4) days in the control group. The difference between the groups was statistically significant (P < .01). Microbial colonization was detected in 5 of the newborns, across the groups; no significant differences were found between the groups (P > .05). Conclusion: In this study, it was determined that clamping the umbilical cord from a distance of 2 cm in vaginally delivered full-term newborns contributed to the shortening of the cord fall time and did not affect microbial colonization.